Post–Glucose Load Measures of Insulin Resistance and Prognosis of Nondiabetic Patients With Ischemic Stroke. Issue 1 (January 2017) - Pan, Yuesong; Jing, Jing; Chen, Weiqi; Zheng, Huaguang; Jia, Qian; Mi, Donghua; Li, Hao; Zhao, Xingquan; Liu, Liping; Wang, Chunxue; Gaisano, Herbert Y.; He, Yan; et al.
Abstract : Background: Insulin resistance is associated with an increased risk of cardiovascular events in the general population. This study aimed to estimate the association between post–glucose load measures of insulin resistance and prognosis of nondiabetic patients with ischemic stroke. Methods and Results: Data were derived from the ACROSS‐China (Abnormal Glucose Regulation in Patients with Acute Stroke across China) registry. Patients with ischemic stroke without a history of diabetes mellitus were included. Two post–glucose load measures of insulin sensitivity, the insulin sensitivity indices ISI(composite) and the ISI0, 120, were calculated. Outcomes included stroke recurrence, all‐cause death, and poor functional outcome at 12 months. Among 1203 patients, 63.3% were male with an average age of 62.1 years. At 12 months, 168 (14.4%) patients had recurrent stroke, 111 (9.2%) had died, and 288 (24.4%) had poor outcome. After adjustment for potential covariates, the first quartile of the ISI(composite) was associated with increased 12‐month stroke recurrence (adjusted hazard ratio 2.02, 95% CI 1.28–3.18, P =0.003), death (adjusted hazard ratio 2.78, 95% CI 1.59–4.86, P <0.001), and poor outcome (adjusted odds ratio 2.67, 95% CI 1.69–4.21, P <0.001) compared with the fourth quartile. Similar results were observed for the ISI0, 120 but with a larger magnitude of association. Using a multivariable regression model with restricted cubic spline, we found an L‐shaped association between the insulin sensitivity indices and the risk of each end point. Conclusions: In this large‐scale registry, post–glucose load measures of insulin resistance with the ISI(composite) and the ISI0, 120 were associated with 12‐month poor outcomes of nondiabetic patients with ischemic stroke.